Penggunaan Fly Ash dalam Pembuatan Bata Beton untuk Meningkatkan Daya Kuat Tekan - Napitupulu, Robert; Triyanto, Romy Ade; Juanda, Juanda (Politeknik Negeri Lhokseumawe, 2025)
Coal is an alternative energy that is used as energy for electricity generation and so on. The results of burning coal produce several wastes that are difficult to process and reuse, one of the wastes produced is fly ash, fly ash waste has several contents similar to cement material, one of which is silica. Use of fly ash as an additive to concrete bricks. This research aims to determine the effect of using fly ash as an additional material on compressive strength tests on concrete bricks and to determine the highest and lowest values of the composition of fly ash and sand. In this research, we will use the full factorial method to determine the number of specimens that will be made in the research, variations in the composition of fly ash: sand used are 30%: 40%, 20%: 50%, and 10%: 60%, with a ratio of cement: water fixed 2 : 1 and drying for 3 and 5 days. Compressive strength testing will be carried out on 6 specimens with 3 replications on each specimen so that the total number of specimens tested is 18 specimens. Based on the results of the best compressive strength test on specimen No.1 with a mixture of fly ash (30%): sand (40%), with a drying time of 3 days, the average maximum strength was 56,86 kg/cm2.